2018
DOI: 10.3126/jucms.v6i2.22494
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Iron Deficiency Anemia in Anemic Patients: A Hospital Based Study

Abstract: Introduction: In developing countries like Nepal, iron deficiency anemia (IDA) is one of the major concern. The high rate incidence has been related to insufficient  iron  intake, accompanied  by chronic  intestinal  blood  loss  due  to parasitic  and  malarial infections. Therefore, a study was conducted to evaluate the prevalence of IDA in anemic patients of Universal College of Medical Sciences-Teaching Hospital (UCMS-TH), South Western region, Nepal. Material and Method It was a hospital based cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Our study showed IDA was common in female 64 (79.01%). Similar results were obtained by Alalimi et al 7 and Mishra et al 8 in their study and they concluded that inadequate intake of dietary iron, inadequate intake of dietary micronutrients, lack of awareness of iron deficiency, excessive menstrual loss, pregnancy and nutritional status were the possible cause.…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed IDA was common in female 64 (79.01%). Similar results were obtained by Alalimi et al 7 and Mishra et al 8 in their study and they concluded that inadequate intake of dietary iron, inadequate intake of dietary micronutrients, lack of awareness of iron deficiency, excessive menstrual loss, pregnancy and nutritional status were the possible cause.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies conducted to analyse the factors associated with anaemia among WRA in Nepal have only explored a few specific individual and household factors (Chandyo et al, 2007; Gautam, Min, Kim, & Jeong, 2019; Harding, Aguayo, Namirembe, & Webb, 2018), and some are based on the analysis of a specific sample or subnational data (Baral & Onta, 2009; Mishra, Marasini, Gupta, Agrawal, & Gautam, 2018; Sinha, Majumdar, & Yadav, 2011). For instance, a study conducted by Gautam et al in 2019 (using 2016 Nepal Demographic and Health Survey [NDHS]) identified that source of drinking water, women's use of hormonal contraception, overweight/obesity and smoking status were significantly associated with anaemia (Gautam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This result of the present study differs from the findings of Mishra et al, in which the most affected ( 42.55 % ) age group was from 21 -40 years. 17 In a study by Kim et al, it was seen that the prevalence of anemia was 12.3 % in men of 70 years and older. 18 This study was confined within National Medical College, Birgunj so the findings may not be viewed as a good representation of the whole region (as patients of this region seek treatment from other health centres as well).…”
Section: Discussionmentioning
confidence: 97%